Oridonin Prolongs the Survival of Mouse Cardiac Allografts by Attenuating the NF-κB/NLRP3 Pathway - Du, Xiaoxiao; Que, Weitao; Hu, Xin; Yu, Xiao; Guo, Wen-Zhi; Zhang, Shuijun; Li, Xiao-Kang (Frontiers in Immunology, 2021)
Background Oridonin (Ori), the main bioactive ingredient of the natural anti-inflammatory herb Rabdosia rubescens, could be a covalent inhibitor of the NLRP3 inflammasome. Solid organ transplantation provides a life-saving optional therapy for patients with end-stage organ dysfunction. The long-term survival of solid organ transplantation remains restricted because of the possibility of rejection and the toxicity, infection, cardiovascular disease and malignancy related to immunosuppressive (IS) drugs. However, the pathogenic mechanisms involved remain unclear. The ideal IS drugs to prevent allograft rejection have not been identified. Here, we investigated whether Ori could prolong the in vivo survival of completely mismatched cardiac allografts. Methods The cardiac transplantation models were conducted among 3 groups of mice from C57BL/6NCrSlc (B6/N) or C3H/HeNSlc (C3H) to C3H: the syngeneic and the allogeneic group recipients were treated with vehicle of Ori; Ori treatment group, in which the recipients were transplanted hearts from MHC-I mismatched donors and treated with different dosages of Ori from post-operative day (POD) 0 to 7. Then we investigated the effect of Ori on bone marrow-derived dendritic cell (BMDC) and allogeneic mixed lymphocyte reaction in vitro. Results Ori with 3, 10, and 15 mg/kg Ori could prolong the survival (MST = 22.8, 49.2 and 65.3 days, respectively). We found that infiltrating CD8+ T cells and macrophages were decreased, and regulatory T cells (Tregs) were expanded in allografts on post operation day 7. And the mRNA level of IL-1β and IFN-γ of allografts were downregulated. Mechanistically, Ori-treated bone marrow-derived dendritic cells (BMDCs) suppressed T cell proliferation and IFN-γ+CD4+ T cell differentiation, along with the expansion of Tregs and IL-10+CD4+ T cells. Ori inhibited NLRP3 expression; attenuated NF-κB and IκBα phosphorylation in LPS-activated BMDCs; downregulated NLRP3, Caspase-1, IL-1β, IL-18, and IFN-γ; and upregulated IL-10 expression. Conclusions Our findings highlight the potential of Ori as a novel and natural IS agent to improve transplant tolerance. Ori could exert immunosuppressive activity through decreasing IL-1β and IL-18 production and Th1 differentiation and proliferation and expanding Tregs via inhibiting the NF-κB/NLRP3 signaling pathway.